Hunting security bugs - Gallagher, Tom (Secure software development series., 2006)
"Finding security flaws is now a fundamental development task, yet there has not been adequate documentation of the process used to find security bugs-until now. Before the Internet, computers were deployed in trusted environments and software development and testing practices emphasized functionality over security. As networking technologies emerged, though, times changed and people began to connect their computers together, instead of deploying in silos. However, development and testing practices did not account for attacks that could be mounted over networks." --Microsoft.